2009
DOI: 10.1111/j.1365-294x.2009.04294.x
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand phylogeography: evolution on a small continent

Abstract: New Zealand has long been a conundrum to biogeographers, possessing as it does geophysical and biotic features characteristic of both an island and a continent. This schism is reflected in provocative debate among dispersalist, vicariance biogeographic and panbiogeographic schools. A strong history in biogeography has spawned many hypotheses, which have begun to be addressed by a flood of molecular analyses. The time is now ripe to synthesize these findings on a background of geological and ecological knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
236
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(242 citation statements)
references
References 446 publications
(960 reference statements)
6
236
0
Order By: Relevance
“…The three main islands (North, South and Stewart Islands) are encircled by numerous smaller islands [15], the flora of which consists mainly of taxa that have dispersed overwater from New Zealand. Although many of these islands were once connected by land bridges, we focused on four island groups that remained isolated from the main islands during the Pleistocene (Kermadec, Three Kings, Chatham and sub-Antarctic Islands; see [16]). In particular, we focused on the Chatham group (1768 W, 448 S), situated 850 km east of the main islands (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The three main islands (North, South and Stewart Islands) are encircled by numerous smaller islands [15], the flora of which consists mainly of taxa that have dispersed overwater from New Zealand. Although many of these islands were once connected by land bridges, we focused on four island groups that remained isolated from the main islands during the Pleistocene (Kermadec, Three Kings, Chatham and sub-Antarctic Islands; see [16]). In particular, we focused on the Chatham group (1768 W, 448 S), situated 850 km east of the main islands (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…More broadly, a recent compilation of molecular phylogenetic analyses of~100 plant and animal groups suggests that only 10% of these are even plausibly of archaic origin predating the vicariant split of Zealandia from Gondwana (Wallis and Trewick 2009). They summarise current opinion on the extent of the Oligocene drowning episode thusly: 'If further paleontological data reveal evidence of uninterrupted fossil records through the Oligocene, complete inundation is made less likely (Winkworth et al 1999;Lee et al 2009).…”
Section: Moa's Ark and Goodbye Gondwanamentioning
confidence: 99%
“…Cooper and Cooper 1995), more recently Waters and Craw (2006) suggested that there is no strong evidence for continuously emergent land through the period (see also Landis et al 2008). Trewick et al (2007) and Wallis and Trewick (2009) asserted that the preponderance of biogeographical evidence favours a scenario of complete submergence during the Oligocene, and some authors have suggested that the entire terrestrial biota arrived via dispersal during the last 22 million years (Landis et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A close phylogenetic relationship is observed between A. audax and Aquila gurneyi from New Guinea and adjacent islands [70,71], and if this represents a proxy for the existence of A. audax in Australia, then the amount of cytochrome b sequence divergence between these lineages (average p distance 3.7%; [70]) rejects the possibility that A. audax is too young to have colonized Tasmania before the LGM. Whereas changes in climate across the LGM have been implicated for extirpation and recolonization of mid-latitude populations in the Northern Hemisphere [72], they appear to have been less influential on species distributions at similar latitudes in the Southern Hemisphere [73,74]. Other animals presently distributed in Tasmania and mainland Australia, including prey species of A. audax, exhibit genetic divergences compatible with occupation of Tasmania during glacial periods [24,[75][76][77].…”
Section: (C) Colonization or Recolonization?mentioning
confidence: 99%